An enterprise system engineering analysis of KC-46A maintenance program decision-making - Blond, Kyle E., author; Bradley, Thomas, advisor; Ender, Tommer, committee member; Conrad, Steven A., committee member; Herber, Daniel, committee member; Ozbek, Mehmet, committee member (Colorado State University. Libraries, 2023)
The KC-46A Pegasus is a United States Air Force (USAF) tanker, transport, and medical evacuation commercial derivative aircraft based on the Boeing 767. It is a top acquisition priority to modernize the USAF's refueling capabilities and is governed by a lifecycle sustainment strategy directed by USAF commercial variant policies aligned to Federal Aviation Administration (FAA) policy. While this strategy provides robust mechanisms to manage the KC-46A's performance during its operations and support phase, opportunity exists for the KC-46A sustainment enterprise to better achieve reliability, availability, maintainability, and cost (RAM C) objectives through enhancing KC-46A maintenance program decision making in the context of USAF and FAA policies. This research characterizes the KC-46A maintenance program as an industrial enterprise system governing the maintenance, repair, overhaul, and modification of KC-46A aircraft. Upon this basis, enterprise systems engineering (ESE) characterizes the KC-46A maintenance program and identifies decision making improvement opportunities in its management. Canonical ESE viewpoints are tailored to abstract the organizations, processes, and information composing KC-46A maintenance program decision making and model how decision support methods can better achieve KC-46A sustainment enterprise objectives. A decision making framework then evaluates the RAM C performance of KC-46A maintenance tasks as part of the KC-46A Continued Analysis and Surveillance System (CASS) program. The framework's heuristics classify the compliance, effectiveness, and optimality of a maintenance task to prescribe KC-46A CASS responses. A rule based expert system applies this framework and serves as the knowledge engine for the KC-46A CASS decision support system referred to as the "Pegasus Fleet Management Tool." A focus group of KC-46A sustainment experts evaluated the framework and produced consensus that it advances the state of the art in KC-46A maintenance program decision making. A business case analysis roadmaps the programmatic and technical activities required to implement the framework in PFMT and improve KC-46A sustainment.
Keywords: enterprise systems engineering; reliability; USAF; maintenance; commercial derivative aircraft; sustainment